Interpretasi Nilai Qurani dalam Film Setetes Embun Cinta Niyala : (Studi Semiotika Charles Sanders Peirce) - Ida Lailatin; Febriyanti Febriyanti; Nadifa Nisaul Afni Nailu Fari; Luthfi Rahman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research discusses the representation of Quranic values in the movie Setetes Embun Cinta Niyala through the Charles Sanders Peirce semiotic approach. Movies as visual media are not only entertainment, but can also be a means of da'wah and moral education. This research aims to reveal how the sign structure (icon, index, symbol) is used to represent Quranic messages, and how the meaning of the sign is interpreted by audience. The method used is descriptive qualitative with observation techniques of scenes in the movie that contain Islamic values. The analysis technique was carried out using the Charles Sanders Peirce Semiotics method. The results of the analysis show that this film explicitly and implicitly displays Quranic messages through visual representations (prayer rugs, prayers, social interactions) and verbal (dialog, quotations of Qur'anic verses). Values such as tawakkal, filial piety, honesty, brotherhood, and sharia restrictions on marriage are displayed by referring to the verses of the Qur'an, which are reinforced through symbolic meaning based on Peirce's theory. This research shows that film can be an effective medium in conveying religious and moral messages, especially when the signs in the film are analyzed in depth through a semiotic approach.